PERUBAHAN FISIOLOGIS AND BIOKHEMIS BENIH KEDELAI YANG DIINFUS DENGAN KINETIN SELAMA PENYIMPANAN - Marwanto Marwanto (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2005)
Soybean seeds deteriorate rapidly when stored under unfavorable conditions and kinetin infusion prior to storage may reduce the rate of seed deterioration. To answer this hypothesis, soybean seeds were permeated with kinetin at 1.0 mM before storage in Agronomy Laboratory on July 2000 at 15 0C and 30 0C for up to 6 months, and their germination, germination after accelerated aging, speed of germination (T50), electrical conductivity and respiration rate were compared with those of untreated seeds stored under the same conditions. The treatments were arranged in a split plot design with three replications. Treated seeds maintained a higher germination and germination after accelerated aging, showed a more rapid germination, a greater cell membrane integrity and a higher respiration rate than untreated seeds irrespective of either storage temperature or storage period, whereas untreated seeds showed a rapid decline in the five seed quality indicators. By four months of storage at 30 0C, treated seeds retained a high level of germination (>80%), medium level of germination after accelerated aging (65%) and a high speed of germination (around 40 hours), while untreated seeds showed a rapid decline in the three seed quality indicators, germination percentage being less than 80%, germination after accelerated aging being less than 50% and speed of germination being higher than 55 hours. Therefore, it is concluded that kinetin infusion prior to storage, in addition to the acceleration of germination, slowed the rate of seed deterioration irrespective of storage temperature through the improvement of cell membrane integrity and seed respiration.